PEMETAAN SPASIAL DAN TEMPORAL STATUS PEMANFAATAN IKAN KERAPU DI PERAIRAN TELUK SALEH, NUSA TENGGARA BARAT - Darmawan, Regi; Wiryawan, Budy; Kleinertz, Sonja; Purbayanto, Ari; Yulianto, Irfan (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
The Saleh Bay is one of the bays in West Nusa Tenggara utilized as the grouper fishing ground. However, in the previous spawning potential ratio study, some grouper species have been overexploited in Saleh Bay. This study aimed to estimate the status of grouper utilization with a catch per unit effort (CPUE) approach and the spatio-temporal fishing intensity of grouper in fishing grounds in Saleh Bay. Data were gathered using the fish landing data and geo-reference of fishing ground grouper in Saleh Bay. This study used several methods: descriptive analysis, catch per unit effort, and spatial-temporal analysis. The result showed that the catch unit effort positively impacts production, with the increasing trend of grouper fishing in Saleh Bay waters. The CPUE value in 2016 was 2.82 kg/trip, while in 2020, it increased to 3.99 kg/trip. Spatially and temporally, fishers caught grouper around small islands such as Liang Island, Dempu Island, Lipan Island, Takat Nusa Pudu, and Rakit Island. The highest intensity of grouper fishing around the marine protected area, namely Rakit Island, Liang Island, and Ngali Island. Keywords: catch per unit effort, fishing ground, grouper, Saleh Bay